The Influence of Financial Knowledge on Financial Behavior and Financial Satisfaction on Pelita Indonesia Students - Harry Patuan Panjaitan; Nicholas Renaldo; Suyono Suyono (Jurnal Manajemen Indonesia, 2022)
The 2020 pandemic situation caused more than 60 percent of dissatisfaction with the survey results to the current financial situation. From the same small survey, it was found 34 percent of respondents showed poor financial habits. This study aims to determine the effect of Financial Knowledge on Financial Behavior and Financial Satisfaction. The sample in this study was 246 people using purposive and convenience sampling techniques. Data processing using path analysis with a Bayesian approach. The results showed that there was a significant influence of Financial Knowledge on Financial Behavior, Financial Knowledge on Financial Satisfaction, and Financial Behavior on Financial Satisfaction. Improved Financial Knowledge, both directly and indirectly, will greatly impact on Financial Satisfaction and really needs to be improved. Central Bank can provide financial knowledge supplies to lecturers of certain subjects so that it can be passed on to students. Keywords—Bayesian Approach; Behavior; Knowledge; Satisfaction